Contesting the Gothic : fiction, genre and cultural conflict, 1764-1832 - Watt, James (Cambridge University Press, 2013)
Charting its vicissitudes from Walpole to Scott, James Watt shows the Gothic to have been a heterogeneous body of fiction, characterised at times by antagonistic relations between writers or works. He examines the novels' political import, and looks ahead to the fluctuating critical status of Scott and the Gothic.